EXAMINATION ELIGIBILITY VERIFICATION AND ATTENDANCE SYSTEM USING QUICK RESPONSE CODE - MUHAMMAD, BASHIR ABDULLAHI; ZAHRA'U, MUSA NURA; LAWAL, MUSA JIYA (I-Manager's Journal on Digital Signal Processing, 2018)
In many institutions, during each examination, the only requirement that is needed for a student to enter examination hall is his/her identity card, which is checked for authenticity and validity of the student. This process does fail to identify if such a student is eligible to write that examination. Currently with the high ratio of students to invigilators in many examination halls, using only ID card for verification does not show whether a student has registered for a subject or not. As a result, some students make use of this loophole to request the assistance of another student from another level or other department to help them write the exam on their behalf. This act is impersonation and thus, is an act of examination malpractice. In this paper, an examination eligibility verification system using quick response code was developed. The EEV system was designed using UML diagrams and implemented using JavaScript, Cascading Style Sheet, and HTML5 in Microsoft Visual Studio Code for the front-end, and PHP and MySQL relational database management system for the back-end. The EEV system was validated using a smartphone to scan the QR code generated. It was observed that the system took four seconds to verify a student's eligibility status. This shows that 300 students can be verified in 20 minutes. Furthermore, it provides a log file that keeps track of eligible students, which serves the purpose of attendance. So, the EEV system was friendly, secures and reliable, and has fast response time.